STUDY AND APPLICATIONS OF DETECTION METHOD FOR MACHINING QUALITY OF HELICAL SURFACE - DONG ZongZheng; KUANG YuChun; ZHANG Cong; YU JiangHai (Jixie qiangdu)
In order to control and improve the manching quality of helical surface,studied method about the measurement,put forward a analysis method of machining error based on the data of contact digital measuring technique. According to the characteristic of spiral curved surface,the characteristic line is measured by using the custom fixture and the cross measuring head. The model of lead helix、measuring section extraction and machining error are proposed. To ensure the accuracy and efficiency,the model algorithm and data input and visualization is completed. The results of rotor machining error show that it can measure the helical surface meeting rapid detectio requirements through the method and has certain application value.